PENGARUH PENGGUNAAN ENDOCARP SAWIT UNTUK STABILISASI TANAH LUNAK PEATLAND - Misnawati; Marlia Adriana; Norminawati Dewi; Suhaimi (Jurnal Humaniora Teknologi, 2023)
During this use Endocarp mostly produced by the oil palm plantation industry. Research is done by mixing Endocarp oil palm that has been sun-dried with maximum dry conditions along with soft clay soil with a content of Endocarp 4%, 6%, and 8%. The sample used in this study is a samples undisturbed , and samples disturbed prepared in the laboratory by mixing clay and Endocarp with a variation of the mixture used is 4%, 6%, and 8% from one bag of clay weighing 2 kg. There is a mix Endocarp the following results were obtained: equal to 1.37 gram/cm3 with a water content of 24.72% (original soil). The CBR value of the mixture Endocarp this study 4%, 6%, 8% obtained the result that the CBR value is mixed Endocarp 4% has the greatest CBR value, which is equal to 7.99% (Unsocked) and 6.69% (socked). The UCT value of the soil will increase in the presence of a mixture Endocarp until mixed Endocarp added by 4% and the UCT value will decrease after the mixture Endocarp above 8% fiber content, maximum UCT value is produced in the mixture Endocarp 4% with a qu value of 0.9295 kg/cm2. The value of the soil shear resistance (su) on the test Vane Shear Test continued to improvement in the mixture Endocarp as much as 4% worth 92 kPa (25 blow condition).